Masticatory performance and quality of life of HK older adults - Dr Elaine Kar Man Choong; Dr Katherine Chiu Man Leung; Prof. Edward Chin Man Lo (Elsevier, 2023)
Aim or Purpose: To examine the association between masticatory performance (MP) of older adults and their oral health-related (OHRQoL) and general health-related quality of life (HRQoL). Materials and Methods: 700 older adults aged ≥60 were recruited from outpatient clinics and community centers in Hong Kong(HK). Participant's objective MP was assessed through a* value of colour-changeable chewing gum, maximum anterior, and posterior bite force. Subjective MP was evaluated with a validated chewing function questionnaire(CFQ). The validated Cantonese version of the Geriatric Oral Health Assessment Index(GOHAI) and 12-item Short-Form Health Survey(SF-12) were used as the OHRQoL and HRQoL measures respectively. Other variables included socio-demographic characteristics, smoking habit, disease counts, handgrip strength, Clinical Frailty Scale(CFS), Katz Index of Independence in Activities of Daily Living(ADL), Lawton Instrumental ADL(C-IADL), Mini Nutritional Assessment-Short Form(MNA-SF), and HK 5min-Montreal Cognitive Assessment scores. Results: The mean GOHAI, PCS-12 and MCS-12 (physical and mental component summary of SF-12) scores were 51.5, 46.4 and 52.5 respectively. Multiple linear regression analysis revealed that participants who were older, had higher maximum posterior bite force, CFQ scores, Lawton C-IADL scores, and lower disease counts had higher GOHAI scores, indicating better OHRQoL. Regarding HRQoL, PCS-12 score had significant association with CFQ score, gender, disease counts, CFS and Lawton C-IADL score; whereas MCS-12 score was significantly related to CFQ score, age, disease counts, CFS, MNA status and handgrip strength. Conclusions: Better subjective MP as indicated by higher CFQ score was associated with better OHRQoL and HRQoL status among older adults in HK. Of the three measures of objective MP, only maximum posterior bite force had a significant association with OHRQoL.